The Effect Of Evaluation Performance On Adlib.Id Employee Loyalty (Convection) Through Job Satisfaction - Nauzal Zamzami; Rita Tri Yusnita; Dudu Risana (Journal of Indonesian Management, 2023)
This study aims to determine the effect of performance elvaluation on employee loyalty Adlib.Id (convection) through job satisfaction. The method used is a quantitative approach with a research sample of 40 respondents from Adlib.Id Convection Employees. The data used are primary data and secondary data. The analysis tool used in this study is path analysis using SPSS version 25. Based on the results of this study, it shows that performance evaluation has a direct effect on employee loyalty. Based on the results of the study, Performance Evaluation has no effect on Job Satisfaction, not significant effect. Based on the results of Job Satisfaction, the effect on Employee Loyalty does not have an insignificant effect. Based on the results of the study, the effect of Performance Evaluation on Employee Loyalty through Job Satisfaction is not significant, it has no effect.